Remote medical diagnostics, health-state monitoring systems, and point-of-care tests as tools reinforcing the patient’s subject role in an ageing society - Susło, Robert; Drobnik, Jarosław; Mastalerz-Migas, Agnieszka (Lekarz POZ, 2017)
The proportion of elderly people in the Polish population is expected to rise in the coming years, and already the social and medical security systems are overloaded and insufficient. A supporting tool for medical care efficiency can be modern technologies, especially telediagnostics. Everyday life medicalisation, becoming even deeper with age, causes the border between privacy and the medical sphere to blur. Not only specialised medical devices but also more and more everyday use devices enable measurement or monitoring and transmitting of data on the user’s activity or vital parameters. Point-of-care tests are attractive both to patients – reinforcing their feeling of being subjects, of being independent, and allowing them to keep their privacy and intimacy during the test – and to medical personnel, who benefit not only from the ability to perform fast urgent diagnostics directly at the office, bypassing the burdensome logistics of performing the tests in the traditional way, especially on old age patients, but also from saving visit time in cases when the test results show no abnormalities. The vast range of point-of-care tests was enriched lately by the test for gluten intolerance, which focuses the rising interest of patients, and the test for iron deficiency, risk of which is quite common in the population. Dynamically developing tele-diagnostics and remote health-state monitoring systems together with a wider and wider range of point-of-care tests present as increasingly valuable tools supporting traditional methods of primary care physician’s diagnostics, especially in case of old age patients.